Police and Penitentiary Activities in Colonial Turkestan - Nigora Rakhimdjanova (International Journal on Integrated Education, 2022)
The article describes the organization and powers of police and penitentiary services in colonial Turkestan in the late 19th-early 20th century. On the basis of statistics-rich archival documents, the activities of the police, prison and other power structures have been analysed.